Getting the most out of your doctorate : the importance of supervision, networking, and becoming a global academic - Dollinger, Mollie (Surviving and thriving in academia, 2019)
Beyond the doctoral thesis itself, the most significant factors in the progression of PhD candidature and early academic careers are: the relationships between the researcher and their supervisor(s), the ability to network, and understanding one's place in the global research arena. Navigating these critical factors and moving from a novice to expert, is a critical undertaking for every PhD candidate and a process that will continue for years following one's PhD. In this book, scholars from around the world offer practical advice on how to get the most out of one's doctorate. Readers will get helpful tips on how to sustain healthy and long-lasting relationships with their supervisors, learn how to develop their networks, and understand the important changes impacting the modern PhD candidate.